Gerencia de la academia:aproximación sistémica para su mejoramiento - Bejarano Garzón, Lilian Astrid; Meza Álvarez, Joaquín Javier (Ingeniería, 2000)
Academic quality means, continuos Improvement which leads to a higher academic and professional efficiency. One goal of present investigation was to provide both student andteacher an upto date presentation of a reflection named proactive mental development which improve not only acquire information about the structure of our enviroment but to interact effectively with it. A second aim of this investigation was to show that is possible to change academic culture focus and to be anchor to an old learning model basic only in contents but not looking at new paradigm learning process.